2014
DOI: 10.1016/j.neuron.2014.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s Disease Genetics: From the Bench to the Clinic

Abstract: Alzheimer’s disease (AD) is a clinically heterogeneous neurodegenerative disease with a strong genetic component. Several genes have been associated with AD risk for nearly twenty years. However, it was not until the recent technological advances that allow for the analysis of millions of polymorphisms in thousands of subjects that we have been able to advance our understanding of the genetic complexity of AD susceptibility. Genome wide association studies and whole exome and whole genome sequencing have revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
308
0
9

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 411 publications
(328 citation statements)
references
References 173 publications
4
308
0
9
Order By: Relevance
“…In addition, this study confirmed that APOEe4, CR1, BIN1, EPHA1, and CD33 were associated with LOAD in African Americans as previously confirmed in Caucasians, highlighting the importance of these variants in disease risk by replicating the associations in multiple ethnically diverse populations. These studies demonstrate that some AD risk loci appear to have similar effects among different populations while others seem to be population-specific [46].…”
Section: Finding Genetic Risk Factors In Diverse Ethnic Groupsmentioning
confidence: 67%
“…In addition, this study confirmed that APOEe4, CR1, BIN1, EPHA1, and CD33 were associated with LOAD in African Americans as previously confirmed in Caucasians, highlighting the importance of these variants in disease risk by replicating the associations in multiple ethnically diverse populations. These studies demonstrate that some AD risk loci appear to have similar effects among different populations while others seem to be population-specific [46].…”
Section: Finding Genetic Risk Factors In Diverse Ethnic Groupsmentioning
confidence: 67%
“…These neuropathological hallmarks of AD include the extracellular deposition of neurotoxic amyloid-β (Aβ) in the form of amyloid plaques and an accumulation of intracellular neurofibrillary tangles composed of hyperphosphorylated tau 3 . Despite progress in understanding risk factors contributing to AD progression, the mechanisms involved in disease progression are not fully understood and long-term treatments, reversing the cellular disease process in the cortex, are elusive.There has been considerable success in identifying genetic risk factors for AD 4 . While autosomal dominant mutations in three genes (APP, PSEN1, and PSEN2) can explain earlyonset (< 65 years) familial AD, these account for only 1-5% of the total disease burden 5 .…”
mentioning
confidence: 99%
“…A common emerging theme in the research field of age-related neurodegenerative diseases is that of endosomal dysfunction [1]. Specifically in Alzheimer's disease (AD), primary evidence pinpointing the endosome as the intracellular site of dysfunction was described in a seminal series of histological studies performed by Cataldo et al [2].…”
mentioning
confidence: 99%